KENYA’S ENVIRONMENTAL DIPLOMACY AT UNEP IN MOBILISING CLIMATE ADAPTATION FINANCE - Salome Nzuki; Dudy Heryadi; Siti Aliyuna Pratisti (Intermestic: Journal of International Studies, 2026)
Climate change causes devastating socio-economic and environmental effects. Developing countries like Kenya that contribute little to global greenhouse emissions are disproportionately affected. This paper explores how Kenya’s environmental diplomacy at the United Nations Environment Programme (UNEP) contributes to mobilisation of climate adaptation finance. The study is guided by concepts of environmental diplomacy and climate finance, utilizing qualitative research methods through semi-structured interviews and documentary analysis. The findings demonstrate that through environmental diplomacy at UNEP, Kenya strengthens diplomatic visibility, builds coalitions and global partnerships that would indirectly increase the chances of securing climate finance. Nonetheless, some drawbacks hinder the transformation of Kenya’s diplomatic leverage into concrete financial outcomes. These include geopolitics, institutional separation of UNEP and United Nations Framework Convention on Climate Change (UNFCCC), competition, bureaucracy and national institutional capacity. This research contributes to academic discourse on environmental diplomacy, affirming that to effectively mobilise climate finance, a country must balance between diplomacy, reinforcing national institutions and engagement with global governance structures.